2016
DOI: 10.1097/ncq.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and Medical Perceptions of a Hospital Rapid Response System

Abstract: Perhaps no other patient safety intervention depends so acutely on effective interprofessional teamwork for patient survival than the hospital rapid response system. Yet, little is known about nurse-physician relationships when rescuing at-risk patients. This study compared nursing and medical staff perceptions of a mature rapid response system at a large tertiary hospital. Findings indicate that the rapid response system may be failing to address a hierarchical culture and systems-level barriers to early reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 21 publications
0
82
0
Order By: Relevance
“…Clinicians who work together as a team to achieve specific goals have specialised work roles involving task‐specific competencies; they share resources and communicate to collaborate and adapt to change . However, individual clinicians bring with them various attitudes, knowledge, skills and levels of experience, including societal perceptions of group hierarchy that impact on decision‐making . There is evidence that NTS teamwork training is necessary to enhance clinicians' understanding of roles, to improve communication practices, and to enable shared decision‐making among team members .…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians who work together as a team to achieve specific goals have specialised work roles involving task‐specific competencies; they share resources and communicate to collaborate and adapt to change . However, individual clinicians bring with them various attitudes, knowledge, skills and levels of experience, including societal perceptions of group hierarchy that impact on decision‐making . There is evidence that NTS teamwork training is necessary to enhance clinicians' understanding of roles, to improve communication practices, and to enable shared decision‐making among team members .…”
Section: Introductionmentioning
confidence: 99%
“…A report by Cretikos et al () highlighted RR as the neglected vital sign and in spite of improvements in care such as EWS, failure to assess RR is still commonplace. Conversely, more recent studies have established that nurses are aware of the significance of RR (Douglas, Osborne, et al, ; McDonnell et al, ). Measurement of RR is classed as a simple, cost effective and probably the most important vital sign (Kellett & Sebat, ), yet also often called the vexatious vital sign, as time, skill and patience are required (Kellett & Sebat, ; Lovett, Buchwald, Stürmann, & Bijur, ).…”
Section: Discussionmentioning
confidence: 99%
“…Professional relationships between nurses and doctors have long been seen as problematic (Chalwin, Flabouris, Kapitola, & Dewick, ; Chua et al, ; Douglas, Osborne, et al, ; Kitto et al, ; Massey, Chaboyer, & Aiken, ). A qualitative study identified that the perceived hierarchy between the medicine and nursing professional may halter escalation of care (Chua et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…, Douglas et al . ) are also likely to influence successful adoption in practice (Hills , Douglas et al . ), as reflected in our findings.…”
Section: Discussionmentioning
confidence: 99%